Corrections, Inc
A special radio report about money and the politics of criminal justice. The show looks into the correction industry in the U.S. and investigates the claim that corporations, police agencies and prison guard unions help to keep the prisons full. The program includes: Introduction (01:00); Segment A: ALEC (14:30); Segment B: Asset Forfeiture (19:30); Segment C: California Prison Guards (16:30).